Individual, family and social-related factors of eating behavior among Chinese children with overweight or obesity from the perspective of family system - Zhu, Hanfei; Zhao, Kang; Huang, Lidong; Shi, Wenbing; Tang, Chulei; Xu, Ting; Zhu, Shuqin; Xu, Qin; Li, Xiaonan; Chen, Yinhua; Liu, Qianqi; Yang, Linhui (Frontiers in Pediatrics, 2024)
The purpose of the present study is to examine the factors contributing to the development of eating behavior in overweight and obese children from the perspective of the family system. Methods A cross-sectional survey was conducted by using convenience sampling method to select 388 participants in two primary schools in Jiangsu, China. Individual, family and social-related factors were collected. Individual factors included age, gender, ethnicity,single child, social anxiety, depression, physical activity, sleep duration, screen time. Family factors included family environment, family structure, family function, family income, parenting style, parental feeding behavior, home food environment and marital satisfaction. Social-related factors included place of residence, number of surrounding restaurants and social support. Univariate analysis, correlation analysis and multivariate analysis were used to identify factors of eating behavior among Chinese children with overweight and obese.